Management of multiple pregnancies a practical guide - Bricker, L.; Robinson, Julian N.; Thilaganathan, Baskaran (Cambridge University Press, 2023)
Multiple pregnancies are associated with higher risks for both mother and babies. Women with multiple pregnancies have an increased risk of miscarriage, anemia, hypertensive disorders, haemorrhage, and postnatal illness. These pregnancies are more likely to need an operative delivery, and maternal mortality is generally 2.5 times that of singleton births. Fetuses are at increased risk for anatomic and genetic anomalies, growth abnormalities, prematurity, and several physiological problems related to monochorionicity. This book provides a much needed, up-to-date guide to the management of multiple pregnancies. Presented with a uniform approach to all chapters, information is easily navigable, evidence-based, and highly practical. Heavily illustrated, particularly with ultrasound images - the cornerstone of management of multiple pregnancies - this book will appeal to obstetricians and specialists in maternal-fetal medicine, midwives and ultrasonographers and will improve outcomes for mothers and babies.